Hyaluronsäuregele zur Druckregulierung in der Glaukomtherapie - Thaller, Michael Andreas; Böhm, Heike; Lingenfelder, Christian; Geiger, Fania (Der Ophthalmologe, 2018)
BackgroundThe increasing numbers of glaucoma patients and complications occuring during treatment, such as restenosis and hypotony, require new treatment options to prevent blindness in patients. Therefore, the abovementioned problems should be solved to prolong the lifetime of implants and to prevent repeated surgery.ObjectiveCan a novel stent with hyaluronic acid hydrogels (HA gel) as a functional unit be used to regulate pressure in glaucoma therapy in the long term?Material and methodsModel stents were filled with HA gels and it was investigated if these could regulate the pressure and what the underlying mechanism is.ResultsThe results of the investigations showed that the HA gel inside the stent functions as a pressure valve. Under certain equilibrium pressures the HA gel closes the stent and therefore retains the fluid. At a certain overpressure the HA gel enables the fluid to be released and leads to a self-regulated adjustment of the equilibrium pressure.DiscussionThe next step will involve miniaturization of the stents. Experiments will then show if the valve function will also work in the dimensions necessary for an eye implant and if the current problem of hypotension in glaucoma therapy can be solved.